FDI and Economic Growth: A new Look from the Sectoral Perspective - Šimić, Vladimir; Malešević-Perović, Lena (Naše gospodarstvo/Our economy, 2022)
This paper investigates the impact of foreign direct investment (FDI) on economic growth in a sample of 10 ex-socialist European and Asian countries. While the link between FDI and economic growth has been extensively investigated in empirical literature, this paper contributes to this literature by econometrically investigating the effects of FDI inflows in specific sectors using the panel data estimation techniques. In addition to confirming the positive impact of total FDI inflows on economic growth, using the WiiW (the Vienna Institute for International Economic Studies) FDI database, which disentangles the FDI data across different industries, the paper finds significant effects of FDI inflows in manufacturing on growth, whereas FDI inflows in other sectors are only sporadically statistically significant. This finding serves as a basis for further investigation of the specific subsectors (NACE 2-letter classification) within manufacturing, and the empirical investigation finds that not all FDI inflows within manufacturing enhance economic growth.